Perlindungan Hukum Terhadap Suatu Merek Terdaftar Di Indonesia - Manurung, Rachel Wahyunita Theodor; Silalahi, Wilma (USRAH: Jurnal Hukum Keluarga Islam, 2025)
Trademarks, as intellectual works, must be respected and protected to safeguard the interests of individuals and groups. The concept of Intellectual Property Rights (IPR) is outlined as the result of human work that has economic value, and strong legal protection is required to encourage innovation and prevent rights violations. This research employs normative legal methods with secondary data sources, including statutory regulations, books, and scientific articles. The analysis is conducted through statutory approaches and content analysis methods.Law Number 20 of 2016 concerning Trademarks and Geographical Indications is identified as the legal foundation governing trademark rights, which are obtained through the "first to file" registration system. Legal protection encompasses rights recognition, preventive and repressive measures, access to legal assistance, and government accountability. This study highlights challenges in trademark registration and the importance of awareness regarding legal protection to prevent violations, as well as supporting national economic development. The research emphasizes that effective trademark protection serves as a crucial step in safeguarding trademark owners' interests and market integrity. Through comprehensive legal framework analysis, this study demonstrates how proper trademark protection mechanisms contribute to fostering innovation, maintaining fair competition, and strengthening the overall intellectual property regime.Furthermore, the implementation of the "first to file" system under Law Number 20 of 2016 provides certainty and clarity in trademark ownership determination, while establishing clear procedures for registration, enforcement, and dispute resolution. The legal protection framework not only addresses the immediate concerns of trademark holders but also contributes to the broader objectives of economic development and market stability.Therefore, effective trademark protection becomes a pivotal element in maintaining trademark owners' interests and preserving market integrity, ultimately supporting sustainable economic growth and innovation within the national framework.